Tubular doubling of the caecum dome with two phlegmonously altered appendixes in a child - N. A. Okunev; A. I. Okuneva; N. A. Kalabkin; Ju. N. Shabunina (Вестник хирургии имени И.И. Грекова)
Anomalies of the appendix are rare malformations that are most often diagnosed intraoperatively and do not have a specific clinical picture. The article describes a clinical case in a 6-year-old 4-month-old boy who was admitted to the hospital with symptoms of appendicitis. According to urgent indications, diagnostic laparoscopy was performed, during which two phlegmonously altered appendixes were identified. The diagnosis was « Acute phlegmonous appendicitis of two appendixes. Loose periappendicular infiltrate. Congenital developmental pathology: Tubular doubling of the caecum dome with appendixes ». Laparoscopic appendectomy was performed. Thus, this article describes the rare clinical case of tubular doubling of the caecum dome with phlegmonously altered appendixes.